The difference in the composition of gut microbiota is greater among bats of different phylogenies than among those with different dietary habits - Guo, Min; Xie, Siwei; Wang, Junhua; Zhang, Yuzhi; He, Xiangyang; Luo, Pengfei; Deng, Jin; Zhou, Chunhui; Qin, Jiao; Huang, Chen; Zhang, Libiao (Frontiers in Microbiology, 2023)
Bats have a very long evolutionary history and are highly differentiated in their physiological functions. Results of recent studies suggest effects of some host factors (e.g., phylogeny and dietary habit) on their gut microbiota. In this study, we examined the gut microbial compositions of 18 different species of bats. Results showed that Firmicutes, Gammaproteobacteria, and Actinobacteria were dominant in all fecal samples of bats. However, the difference in the diversity of gut microbiota among bats of different phylogenies was notable (P = 0.06). Various species of Firmicutes, Actinobacteria, and Gammaproteobacteria were found to contribute to the majority of variations in gut microbiota of all bats examined, and Aeromonas species were much more abundant in bats that feed on both insects and fish than in those of insectivores. The abundance of various species of Clostridium, Euryarchaeota, and ancient bacterial phyla was found to vary among bats of different phylogenies, and various species of Vibrio varied significantly among bats with different dietary habits. No significant difference in the number of genes involved in various metabolic pathways was detected among bats of different phylogenies, but the abundance of genes involved in 5 metabolic pathways, including transcription; replication, recombination, and repair; amino acid transport and metabolism; and signal transduction mechanisms, was different among bats with different dietary habits. The abundance of genes in 3 metabolic pathways, including those involved in stilbenoid, diarylheptanoid, and gingerol biosynthesis, was found to be different between insectivorous bats and bats that feed on both insects and fish. Results of this study suggest a weak association between dietary habit and gut microbiota in most bats but a notable difference in gut microbiota among bats of different phylogenies.